Rudolph the red-nosed reindeer - Roemer, Larry; Ives, Burl, 1909-; Richards, Billie; Soles, Paul; May, Robert Lewis, 1905-1995; Destiny's Child (Musical group) (New York, NY : Classic Media/Sony Wonder, 2004)
Rudolph is the only reindeer who can save Christmas by guiding Santa's sleigh through the storm using his shining, red nose.
"The original TV classic"--Container.
Adapted from a story by Robert May.
Bonus CD single contains Destiny's Child singing Rudolph the red-nosed reindeer.
Voices: Burl Ives, Billy Richards, Paul Soles.
MPAA rating: Not rated.
DVD, Dolby digital.
Keywords: May, Robert Lewis, -- 1905- -- Film and video adaptations; Santa Claus -- Drama; Christmas plays; Holidays -- United States -- Drama; Video recordings for hard of hearing people; Made-for-TV movies; Based on the book; Feature films; Clay animation films; Animated films; Christmas films